Climate, physiological tolerance and sex‐biased dispersal shape genetic structure of N eotropical orchid bees - Margarita M. López‐Uribe; Kelly R. Zamudio; Carolina F. Cardoso; Bryan N. Danforth (Molecular Ecology, 2014)
Understanding the impact of past climatic events on the demographic history of extant species is critical for predicting species' responses to future climate change. Palaeoclimatic instability is a major mechanism of lineage diversification in taxa with low dispersal and small geographical ranges in tropical ecosystems. However, the impact of these climatic events remains questionable for the diversification of species with high levels of gene flow and large geographical distributions. In this study, we investigate the impact of P leistocene climate change on three N eotropical orchid bee species ( E ulaema bombiformis , E . meriana and E . cingulata ) with transcontinental distributions and different physiological tolerances. We first generated ecological niche models to identify species‐specific climatically stable areas during P leistocene climatic oscillations. Using a combination of mitochondrial and nuclear markers, we inferred calibrated phylogenies and estimated historical demographic parameters to reconstruct the phylogeographical history of each species. Our results indicate species with narrower physiological tolerance experienced less suitable habitat during glaciations and currently exhibit strong population structure in the mitochondrial genome. However, nuclear markers with low and high mutation rates show lack of association with geography. These results combined with lower migration rate estimates from the mitochondrial than the nuclear genome suggest male‐biased dispersal. We conclude that despite large effective population sizes and capacity for long‐distance dispersal, climatic instability is an important mechanism of maternal lineage diversification in orchid bees. Thus, these N eotropical pollinators are susceptible to disruption of genetic connectivity in the event of large‐scale climatic changes.